Efficacy of non-nucleoside reverse transcriptase inhibitor-based highly active antiretroviral therapy in thai hiv-infected children aged two years or less - Thanyawee Puthanakit (2018)
Twenty-six Thai HIV-infected children, aged 2 years or less were prospectively enrolled to receive non-nucleoside reverse transcription inhibitor-based highly active antiretroviral therapy (HAART). Twenty-two children (85%) had World Health Organization clinical stage 3 or 4. The median baseline CD4 cell percentage and plasma HIV RNA were 17% and 5.9 log 10 copies/mL, respectively. The median age at HAART initiation was 9.8 months (range, 1.5-24.0). One child died. The mean CD4 cell percentages at 24, 48, and 96 weeks of treatment were 26%, 31%, and 37%, respectively. The proportions of children with virologic suppression (<400 copies/mL) at week 24 and 48 were 14/26 (54%) and 19/26 (73%), respectively. Non-nucleoside reverse transcription inhibitor-based HAART is safe and effective in HIV-infected young children in a resource-limited setting. © 2009 by Lippincott Williams & Wilkins.